Effect of Acacia honey drink consumed pre and during exercise on glucose metabolism, total antioxidant status, and running performance in the heat - Mohd Sukri, Nursyuhada; Foong, Kiew Ooi; Chee, Keong Chen; Kuttulebbai Naina Mohamed Salam, Sirajudeen (Kulliyyah of Medicine, IIUM, 2022)
Introduction: This study investigated the effects of Acacia honey drink on glucose metabolism, plasma total antioxidant status, selected physiological parameters and time trial running performance in the heat compared to a commercially-available sports drink. Materials and methods: Ten participants completed two endurance running trials in the heat with either honey drink (H) or sports drink (SPD) ingestion. Honey drink or sports drink was ingested one hour prior to the experimental trials. Participants warmed up for 5 min by running at 50% of their respective VO2max, and subsequently ran at 60% of their respective VO2max for 1hour. This was immediately followed by a 20 min time trial running performance. Participants drank 3 mL.kg body weight-1 of cool honey or sports drink every 20 min during the trials. Blood samples were collected for subsequent biochemical analysis. Results: Plasma glucose, insulin, cortisol, total antioxidant status and running performance were not statistically different between H and SPD trials. These findings indicated that Acacia honey drink and sports drink ingested before and during exercise elicited similar effects on glucose metabolism and endurance running performance. Conclusion: Acacia honey has potential to be used as an alternative ergogenic aid for athletes who train and compete in a hot and humid environment.